Analysis of the Influence of Influencer-Based Marketing on New Product Launch Strategies in the Millennial and Gen Z Markets - Nengsih, Widya; Prasetyaningsih, Nila; Ratnawita (CV ODIS, 2025)
In the digital era, influencer-based marketing has become one of the most effective strategies for reaching millennial and Gen Z markets. This study aims to analyze the impact of influencer-based marketing on new product launch strategies, particularly in creating brand awareness, enhancing consumer engagement, and driving purchasing decisions. The research approach uses a quantitative method with data collection through surveys of 250 respondents from the millennial and Gen Z segments in Indonesia. The analysis results indicate that relevant, authentic, and interactive content delivered by influencers has a significant impact on the success of new product launches. Additionally, the level of consumer trust in influencers also affects the effectiveness of the marketing campaign. This research provides practical contributions for companies to design more targeted and relevant influencer-based marketing strategies that align with the characteristics of millennial and Gen Z markets. By understanding the key factors that influence the success of influencer-based marketing, companies can maximize opportunities to effectively introduce new products in an increasingly competitive market.